Social Construction of Batik Community Women Against the COVID-19 Pandemic in Kerek District, Tuban Regency - Sutinah, Sutinah; Siahaan, Hotman; Mustain, Mustain; Mawardi, Rafi Aufa; Wibisono, Rizky Bangun (Universitas Islam Negeri Sunan Ampel, 2025)
One of the MSME-based social communities affected by the COVID-19 pandemic is the Gedog batik community in Kerek District, Tuban Regency. However, women in the Gedog batik community continue to face challenges in understanding and interpreting the COVID-19 pandemic. This study analyzes the social construction of women in the batik community during the COVID-19 pandemic. This study employs Peter L. Berger’s social construction theory, utilising a phenomenological approach. Qualitative research methods were employed in this study, utilising observation and in-depth interviews as data collection techniques with 20 research informants. The data analysis technique in this study uses data collection, reduction (data categorization), data visualization, and conclusion. This study found that the interpretation of women in the batik community towards the COVID-19 pandemic has a dichotomy that pretends to be positive and negative aspects. This is due to their subjective experiences with the COVID-19 pandemic and other health policies. In addition, socio-economic background, social environment, and technology adoption are fundamental bases that contribute to forming the social construction of women in the batik community. The social construction of the COVID-19 pandemic also reflects social processes manifested in practical actions, such as affirmation (positive) or resistance (negative).